Evaluation of the Validity of the Nature Tourism Marketing Model under Sanctions - Naderi Doust, Mahboubeh; Rostami, Mohammadreza; Hosseini, Seyed Hossein; Sanei, Mehdi (Future of Work and Digital Management Journal, 2024)
The aim of the present study is to design a marketing model for nature tourism under sanction conditions. To evaluate the validity of the nature tourism marketing model under sanctions, a quantitative research method was employed for data analysis, and the Smart PLS software was used to implement structural equation modeling (SEM). The statistical population consisted of employees of the Iranian Ministry of Cultural Heritage and Tourism, which spans 31 provinces and includes over three thousand permanent and contractual staff members. However, the sample was selected using convenience sampling. Cochran's formula was used to determine the sample size, which was calculated to be 366 individuals. After extracting the questions, the questionnaire was distributed among the selected individuals and subsequently collected. Investigation of the relationships between variables: After evaluating the goodness-of-fit for the measurement models, the structural model, and the overall model—according to the data analysis algorithm in the PLS method—to confirm or reject the hypotheses, the t-value must be greater than 1.96 or less than -1.96. Values falling between these two thresholds indicate the absence of a statistically significant difference between the calculated regression weights and zero at the 95% confidence level. One of the essential and pivotal topics in tourism planning is determining the position of infrastructure and the current status of this sustainable industry in a given region. Achieving economic dynamism and prosperity in the country requires optimal utilization of infrastructure and identification of inequalities, making the regional stratification of nature tourism areas a necessity. By identifying and ranking infrastructure at the regional level, more effective management of tourists can be achieved.